MISQUOTATION IN SCIENCE: THE CASE OF QUININE SULPHATE FLUORESCENCE / CITATION INEXACTE EN SCIENCE: LE CAS DE LA FLUORESCENCE DE SULFATE DE QUININE - Holmes , J. David (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see pdf